Identifikasi Kenaikan Suhu Minyak Lumas Pada Motor Induk di MV. Manalagi Dasa - Hermanto, Andy; Pradana, Wisnu; Widiatmaja, Arya (LPPM AKMI SUAKA BAHARI CIREBON, 2024)
Lubrication is one aspect that must be paid attention to, remembering that if there is a delay in lubrication or imperfect lubrication, it will result in damage to the parts that rub together. Low lubricating oil pressure is one of the factors causing imperfect lubrication in the engine. The purpose of lubrication for the performance of the main engine is to reduce friction between other components of the main engine. This research was carried out at MV. Manalagi Dasa, the method used in this research was the Fishbone Diagram. The problem formulation of this research is what causes an increase in the temperature of the lubricating oil on the main motor and what is the impact of increasing the temperature of the lubricating oil on the main motor. Based on research that has been carried out, there are several factors that cause less than optimal lubrication of the oil cooler on the main engine, namely engine factors including damage to gaskets, human factors, namely the lack of understanding of the driver about the lo cooler, operational and maintenance method factors, namely incompatibility in implementing the PMS (Plan Maintenance System) as well as environmental factors, namely dirty sea chest filters. Efforts made include repairing or replacing gaskets on the lo cooler plate, the importance of the machinist's understanding of the lo cooler, implementing PMS (Plan Maintenance System), and cleaning the sea chest filter.